Actualización del sistema de control automático de la etiquetadora de frascos bausch strobel del área de penicilinas de Laboratorios Life Biomasa - Herrera Guachamín, Jonathan Giovanny (2016)
The labeling machine of bottles Bausch Strobel operate in the area of penicillins, the equipment has 30 years of use, it is only able to affix labels on round bottles, different updates exerted on the machine have made a series of disconnected devices, which has generated downtime for corrective maintenance, why not satisfied with the production planning which generated problems with the maintenance department. LIFE laboratories as one of the largest pharmaceutical of the country needs to always be at the forefront with technology for making drugs. Engineers LIFE laboratories are familiar with the brand Siemens in the automation and control equipment and projects, which is why an S7-1200 PLC was used with HMI KP-300 Siemens screen. In developing the project team complete characterization and identification of the labeling process was conducted to know the operation of the equipment, check failures and propose improvements which formed the basis for the development of the automatic update control. The process of fixing labels on the bottles is performed by a stepping motor, the labels pass through a set of rollers which tension the belt and then the blank tapes are picked up by driving another motor. A quick out of S7-1200 PLC was used for controlling the speed of this motor actuating a driver. A human machine interface (HMI) was implemented to monitor and control the labeling machine also has a system of visible alarms in the HMI, which allow the operator receive alerts and resolve potential failures with a friendly atmosphere.